As we move along an indifference curve and consume different market baskets containing goods X and Y, the change in satisfaction is equal to

0 votes
    zero, and is represented by the equation 0=MRS=Px(?X)+Py(?Y), where MU=Marginal Utility.
     zero, and is represented by the equation 0=Px(?X)+Py(?Y), where MU=Marginal Utility.
     positive, and is represented by the equation ?Satisfaction=MUx(?X)+MUy(?Y), where MU=Marginal Utility.
     When the change in one good is positive, there must be a change in the opposite direction so that MUx(?X)= -MUy(?Y).
asked Jun 2, 2013 in Economics by anonymous
    

1 Answer

0 votes
When the change in one good is positive, there must be a change in the opposite direction so that MUx(?X)= -MUy(?Y).
answered Jun 3, 2013 by Xyz ~Expert~ (3,650 points)



...